A Review of Smart Materials: Researches and Applications - Qader, Ibrahim Nazem; Kök, Mediha; Dagdelen, Fethi; Aydogdu, Yildirim (TUBITAK, 2019)
Smart materials are a family of materials that are listed in advanced materials. These groups of materials have self-accommodation with environment and they are classified according to their responses, such as physical (pressure, temperature, humidity, light, electric field, magnetic field), chemical (pH, CO2, etc.), or biological stimuli. The smart materials can convert the absorbed energy or their characteristics may undergo a change. Smart materials are getting high attentions due to their commercial applications in either actuator or sensor form. This work demonstrates an exclusive review of different types of smart materials with their specific characteristics, and some related investigations that improved smart material properties. In addition, the applications of smart materials are categorized according to the different application areas, such as medical implantation, reducing waste, and nano engineered systems. © 2019, TUBITAK. All rights reserved.
Akıllı Malzemeler Üzerine Derleme: Araştırmalar ve Uygulamaları
Keywords: Biomedical; Piezoelectric; Robotic; Shape memory alloy; Smart material